Performance evaluation of nanosilica derived from agro-waste as lost circulation agent in water-based mud - Agi, Augustine; Oseh, Jeffrey O.; Gbadamosi, Afeez; Fung, Cheo Kiew; Junin, Radzuan; Jaafar, Mohd Zaidi (KeAi Publishing Communications Ltd., 2023)
Seepage or loss of the mix-water from the drilling muds into the porous and permeable formations is a common problem during drilling operation. The drilling mud design requires a good knowledge of sealing integrity and all the factors influencing the mud to bridge through fractures or pore throat of exposed rocks. Loss circulation materials (LCMs) are commonly introduced into the drilling mud to prevent or minimize filtrate loss. This study investigates silica nanoparticle (SNP) derived from rice husk (RH) termed RH-SNP using the wet-milling method as an LCM in water-based mud (WBM). The impact of the RH-SNP in the enhancement of rheology and filtrate loss control properties of WBM was studied. Subsequently, the sealing integrity of the RH-SNP in a 1 mm and 2 mm simulated fracture for 7 min was determined using a stainless-steel slotted filter disk. The performance of the developed RH-SNP was compared with the widely applied nutshell. The synthesized RH-SNP at amount of 2.0 wt% significantly enhanced the yield point and plastic viscosity of the WBM by 75% and 386%, respectively, and minimized the fluid loss of the WBM by 47% at 80 °F. The enhancement is due to the particles ability to spread and interact efficiently with the WBM. With the use of 1 mm and 2 mm simulated fracture for 7 min, the mud loss volume of the base mud reduced by 50%, 66.7%, 86%, and 90% (for 1 mm) and 40%, 65.7%, 77.1%, and 80% (for 2 mm) with the inclusion of 0.5 wt%, 1.0 wt%, 1.5 wt%, and 2.0 wt% of RH-SNP, respectively. Overall, the results showed that RH-SNP enhanced the seal integrity of the drilling mud and was more resistant to deformation compared to the nutshell. The findings of this study can help for better understanding of the application of RH-SNP as a loss circulation agent owing to its superior ability to seal fractured formation compared with the often used nutshell.